Pengaruh Kualitas Pelayanan PMKU (Pemberitahuan Melakukan Kegiatan Usaha) Terhadap Kepuasan Pengguna Jasa di KSOP Kelas III Talang Duku - Shallyan Angelin; Otri Wani Sihaloho; Dyah Ratnaningsih; Faris Nofandi (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study aims to analyze the influence of service quality on user satisfaction in the process of Business Activity Notification (PMKU) at the KSOP Class III Talang Duku Office. The research is motivated by several on-site challenges, including users’ lack of understanding in completing documents, repeated submissions, system technical issues, and low awareness among companies regarding licensing obligations. This research employed a quantitative approach with data collected through questionnaires and direct observation during the Land Practice (PRADA) program. Based on the results of simple linear regression analysis, a regression coefficient of 0.175 was obtained with a significance value of 0.003, indicating a positive and significant influence of service quality on user satisfaction. The R Square value of 0.133 shows that 13.3% of the variation in user satisfaction can be explained by service quality, while the remaining 86.7% is influenced by other factors outside the model. The t-test results confirm that service quality has a partial effect on user satisfaction, and classical assumption tests indicate that the regression model meets the requirements of normality, linearity, and homoscedasticity. Based on these findings, it is recommended that service quality be improved through user education, the digitalization of technical guidelines, the optimization of the Inaportnet system, and the implementation of an early warning system, in order to make PMKU services more effective, efficient, and in line with user expectations.